Physical Education Teacher Learning Management During the Covid-19 Pandemic at Special School in Pekalongan Residency in 2020 - Larasati, Atika; Sulaiman, Sulaiman; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The purpose of this study was to investigate the planning, implementation, evaluation, and follow-up of physical education learning in special schools throughout the Pekalongan Residency during the COVID-19 pandemic. This is a qualitative type of research. Research respondents were students, teachers, and school principals. Observation, interviews, and documentation are all used to collect data. Data management included research data collection/collection, research data reduction, presentation or data, conclusion drawing, or research data verification. Result: The teacher-led learning to plan at the Special Schools located throughout the Pekalongan Residency is generally consistent with the curriculum; the teacher also creates syllabi and lesson plans; however, the teacher-led assessment activities have not been completed; consequently, the implemented learning is not consistent with the stages of learning implementation, namely opening, core activities, and closure. This is because it is constrained by the ongoing pandemic; teachers’ evaluations of learning are different, considering the characteristics of their students; one of the teacher’s evaluation activities is to assign assignments at the end of the semester, while the follow-up is related to the evaluation’s results. A follow-up program for the outcomes of the learning evaluation has not been implemented in Physical Education and Health at Special Schools throughout the Pekalongan Residency during the pandemic. Conclusions: learning to plan in special schools within the Pekalongan residency is categorized as (SB), learning implementation in special schools within the residency is categorized as (C), learning evaluation in special schools within the Pekalongan residency is categorized as (K), and follow-up on learning evaluation results is categorized as (K).